CGIAR Capacity Development Workshop: Quick comments from participants - International Livestock Research Institute (International Livestock Research Institute, 2013)
Quick comments from participants of a CGIAR Capacity Development Workshop that was hosted by the International Livestock Research Institute (ILRI) in Nairobi from 21-25 Oct 2013.